Recent Advances in Integrated Photonic Jet-Based Photonics; Photonics; Vol. 7, iss. 2 - Minin I. V. Igor Vladilenovich; Liu Cheng-Yang; Geynts Yu. E. Yury Elmarovich; Minin O. V. Oleg Vladilenovich (2020, 2020)
Title screen